Identification, Classification and Ranking of the Causes of Building Collapse in Abuja, Nigeria – A Review - Akuboh, B. O.; Aimola, T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This study examines the incidences of reported building collapses from inception in Abuja, Nigeria from 2008 to 2024 and the attendant increasing loss of lives, properties and injuries, with a view to determining leading causes of building collapses, it’s classification and ranking within the FCT - Abuja. It also highlights the casualties arising from these occurrences. There has been conflicting information on casualties and damages resulting from building collapses in Nigeria perhaps due to ineffective coordination amongst agencies responsible. Findings of this study revealed the leading causes of building collapse in the FCT in decreasing order as to include Use of sub-standard building materials, structural failures, use of quacks, poor or lack of supervision and lack of conduct of geotechnical investigation/inappropriate foundation. A total of thirty (30) cases of building collapses were identified to have occurred in the FCT leading to the confirmed death of at least fifty-seven (57) persons. Recommendations were made in line with the leading causes of building collapse in the FCT.